Constructing the Maritime State of Indonesia in the Framework of Local Autonomy - Kamarudin Kamarudin (Fakultas Hukum Universitas Hang Tuah, 2021)
The research aims at examining how sturdy Indonesia’s maritime state is constructed in the framework of local autonomy by analysing maritime state principles in regulations on recently local autonomy realization in Indonesia. The research constitutes a literature review known as normatively legal research in legal studies. Collected legal sources on research topics are qualitatively analysed in three steps, i.e. to firstly systemise, then to explicate, and to finally evaluate the collected legal sources. The results show that a construction of Indonesia maritime state in the framework of local autonomy is enough sturdy. Local autonomy in managing and utilizing the sea of Indonesia as regulated in Act Number 23 of 2014 on Local Governance is basically conducted in provincial territory by the provincial governments. Nevertheless, district and municipal governments still have the authority in managing and utilizing marine sector. The authority to power and control the sea of Indonesia is dominantly on the central government hands, while the authority to manage and utilize the sea is divided to the central government and provincial and district or municipal governments. Therefore, prosperity from the sea can equally be obtained by local communities and all Indonesian people.